Triple bottom line reporting practices and corporate relationship with host communities in Nigeria (a case study of Niger Delta region) - Udeh, Francis N. P.; Akporien, Fidelis O. (Univerzita Pardubice, 2016)
This study seeks to examine Triple Bottom Line (TBL) reporting practices and corporate relationship with host communities in Nigeria. A survey research design was adopted for the study hence structured questionnaires were administered. The population of the study consists of members of host communities and management staff of companies in the Niger Delta region of Nigeria. Hypotheses stated were tested and analyzed through the use of correlation analysis and one-way analysis of variance (ANOVA) at 5% level of significance with the aid of statistical package for social sciences (SPSS) software (version 16.0). The study findings reveal that there is a significant difference between the level of awareness of host communities members and company management about TBL reports. The result also shows that there is an insignificant relationship between TBL reporting practice and corporate relationship with host communities. Based on the findings of this study, it was recommended amongst others that there is need to adequately localize sustainability reporting framework in line with international standard and that community organization need to imbibe culture of peaceful negotiation in their agitations to avoid negative consequences.
Keywords: triple bottom line; corporate reporting; Niger Delta region; M40; M41; M49